Helen Keller - Wepman, Dennis (New York : Chelsea House, 1987)
Presents a comprehensive profile of Helen Keller, who became deaf and blind at an early age, and profiles her life, long association with her teacher Anne Sullivan, her education and long career as an author, lecturer, and social activist.
Includes bibliographical referencecs (p. 106) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.7
5-8
Keywords: Keller, Helen, -- 1880-1968 -- Juvenile literature; Keller, Helen, -- 1880-1968.; Keller, Helen, -- 1880-1968.; Deafblind people -- United States -- Biography -- Juvenile literature; Blind; Deaf; People with disabilities; Women -- Biography; Blind -- Biography; Deaf -- Biography; Physically handicapped -- Biography; Women -- Biography